PROSES PENCIPTAAN DAN STRUKTUR TARI UDAR GELUNG - Angga Nugraha Saefurridjal; Dindin Rasidin; Ria Dewi Fajaria (TANDIK : Jurnal Seni dan Pendidikan Seni, 2021)
Abstract : This dance work was adopted from the art of Ibing Penca Sobrah in one of the oldest universities in Pasundan, namely Panglipur, which is identified with the professor of the university, namely Rd. Hj. Enny Rukmini Sekarningrat. Famous for the role of sobrah (extra hair) which is used as a weapon against the enemy. The words Udar and Gelung come from the Sundanese language, Udar means to let go, gelung means to tie hair in a circle, Udar Gelung means to untie hair. However, in this work, it means the release of Wanoja's pride by an arrogant Jawara. This dance creation theory uses an objective and subjective approach, focusing on the creations of a choreographer expressed by dancers. All of these processes go beyond exploration, composition and evaluation methods. The type of choreography is group, which is divided into three scenes with the number of dancers being six male dancers and one female dancer. The process of creating works is outlined in the concept of working on traditions with a dramatic structure and originating from the typical traditional movements of pencak silat / Ibing Penca. The moral message raised is that everything will always have a reciprocity and what we do is what we get. Keywords: Udar Gelung, ibing pen sobrah, Wanoja